Biology of Day's Glassy perchlet, parambassis dayi (Bleeker, 1874) from periyar river - Vishnu Priya, K. S. (KUFOS, 2018)
Abstract- The paper embodies the biology of the Day‟s glassy perchlet, Parambassis dayi (Bleeker,1874) from Periyar river. The species inhabits freshwater and estuarine lakes of Western Ghats of Kerala. Parambassis dayi feeds mainly on fishes, crustaceans, insects and worms. The species is a carnivore and fish is the dominant food item. Peak spawning activity of Parambassis dayi is found to be in the month of November. The overall sex ratio showed the predominance of female. 50% of males and females of Parambassis dayi seem to mature in the size range of 9-11 cm and 11-13 cm respectively. Fecundity of Parambassis dayi ranges from 1568-6850. „b‟ values obtained from the length-weight relationship of Parambassis dayi are 2.5429 and 2.9233 for males and females respectively. Population parameters of Parambassis dayi were estimated from length frequency data by using FISAT program. The analysis gave the following Von Bertalanffy growth function (VBGF) parameters, the asymptotic length (L∞) = 18.38 cm, growth coefficient (K) = 0.810/year and tₒ = -0.026 year. Based on these growth parameters, the growth performance index (Φ) was found to be 2.43. Mortality co-efficients of Parambassis dayi were also estimated using FISAT program and the values obtained were total mortality (Z) = 4.51, natural mortality (M) = 1.69 and fishing mortality (F) = 2.82. The exploitation ratio (E) and exploitation rate (U) of Parambassis dayi was found to be 0.63 and 0.61 respectively.